การเตรียมและการตอบสนองโดยการเปลี่ยนสีของวัสดุเชิงประกอบระดับนาโนเมตรพอลิไดแอเซทิลีน/ผลึกนาโนซิงก์ออกไซด์ - ณัฐกานต์ ประกอบแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
This research studies the synthesis of zinc oxide (ZnO) nanocrystals and preparation of polydiacetylene/Zn2+/ZnO nanocrystal nanocomposite. The ZnO nanocrystals synthesized from zinc acetate dehydrate and tetramethyl ammonium hydroxide pentahydrate at various reaction times from 1-2880 min exhibit particle size of 2-6 nm. Then polydiacetylene/Zn2+/ZnO nanocrystal are prepared using 10,12-pentacosadiynoic acid (PCDA) as a monomer. Colorimetric responses of polydiacetylene/Zn2+/ZnO nanocrystals to temperature, pH and organic acid/base are investigated. The results show that polydiacetylene/Zn2+/ZnO nanocrystals change color from blue to purple at lower temperature than that of the previous studied polydiacetylene/Zn2+/ZnO(65 nm). While polydiacetylene/Zn2+/ZnO nanocrystals exhibit reversible color transition at 65-70 °C, polydiacetylene/Zn2+/ZnO(65 nm) change color at 80 °C. Also, polydiacetylene/Zn2+/ZnO nanocrystals show higher sensitivity to hydrochloric acid, sodium hydroxide, salicylic acid and octylamine. Structural analysis indicates relaxation of conjugated backbone and decreasing in strength of ionic interactions between polydiacetylene headgroup and ZnO surface in polydiacetylene/Zn2+/ZnO nanocrystals. Therefore, polydiacetylene/Zn2+/ZnO nanocrystals are disturbed by external stimuli at higher degree than polydiacetylene/Zn2+/ZnO(65 nm).